Kompetensi dan Komitmen dalam Manajemen SDM Kontemporer - Halim, Elsandra Novita; Wahyudi, Fajar; Hartini, Jeanny Kathleen; Cesilia, Rosalina; Primasari, Yustika Dian (Green Publisher Indonesia, 2024)
This study aims to explore the role of competence and commitment in contemporary human resource (HR) management and how they affect organizational performance. In the context of a dynamic and increasingly complex business environment, HR competencies and employee commitment levels are key factors in achieving competitive advantage. This study uses a quantitative approach by distributing questionnaires to HR professionals in various industries to collect data on competency development, HR policy implementation, and employee commitment levels. The results of the study show that there is a significant relationship between good HR competence and high employee commitment to increasing productivity and organizational effectiveness. This research suggests that companies should focus more on developing employee competencies and strategies to increase commitment to face modern managerial challenges. These findings are expected to provide insight for HR practitioners in designing more effective policies and practices to support organizational growth and success.